Trajetória recente e características regionais do consumo de energia elétrica para famílias de baixa renda no Brasil a partir dos dados do programa TSEE (2014-2021) - Edison Benedito da Silva Filho; Guilherme Vampré Homsy (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This study analyzes the recent trajectory and regional characteristics of electricity consumption among low-income families in Brazil, using data from beneficiaries of the Tarifa Social de Energia Elétrica (TSEE) program. It also seeks to assess the impacts of restrictive measures and regulatory changes implemented throughout 2020 to contain the pandemic on the behavior of residential electricity consumers in Brazil. The paper presents a new methodology for evaluating the economic impacts of the TSEE based on detailing the program's data at the regional level, as well as simulating changes in the electricity consumption of the program's beneficiaries in response to changes in the price of the public service offered. Evidence was found that the recent rise in electricity supply costs (notably from 2014 onwards) produced significant and differentiated negative effects for the country's regions, increasing inequalities in access to electricity and in the amount consumed. by low-income households in the country. In turn, the federal government's financial aid measures for low-income families in the period considered most critical for coping with the covid-19 pandemic, in the second half of 2020, do not seem to have produced major impacts in terms of changing their pattern of energy consumption, as well as on the regional discrepancies already observed in the low-income consumer market in Brazil.
Keywords: Q41; Q48; H24; 330; electricity; price elasticity of demand; cross subsidies